Effectiveness of a reeducation program for women, with background of complaint for partner violence, in self-esteem and the construction of gender, Huanuco 2017 - Ayala Albites, Flor María (2018)
The educational programs in health care allow to raise the knowledge and modify the behaviors and affects that threaten the health through the opportune action, in the primary, secondary levels and intervention in rehabilitation or tertiary prevention. The objective of the research article was to determine the effectiveness of a reeducation program for women with a history of reporting for partner violence, self-esteem and gender construction. The design corresponds to the quasi-experimental type of repeated measures (pre and post), without control group; where participated of 35 women with denunciation of partner violence in front of family court - Judicial Power in Huánuco, 2017. In the data collection an interview guide was used, the inventory of gender construction for women victims of intimate partner violence. For the inferential analysis, the Student T Test was used to related groups. The reeducation program intervention demonstrated effectiveness in improving the self-esteem and the construction of gender level through the significant change of distorted and stereotyped beliefs of submission and dependence.